2001
DOI: 10.1086/320053
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Flows and Quasars. II. Detailed Models of Feedback‐modulated Accretion Flows

Abstract: Most elliptical galaxies contain central black holes (BHs), and most also contain significant amounts of hot gas capable of accreting on to the central BH due to cooling times short compared to the Hubble time. Why therefore do we not see AGNs at the center of most elliptical galaxies rather than in only (at most) a few per cent of them? We propose here the simple idea that feedback from accretion events heats the ambient gas, retarding subsequent infall, in a follow up of papers by Binney & Tabor (1995, BT95… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
377
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 356 publications
(397 citation statements)
references
References 73 publications
18
377
0
2
Order By: Relevance
“…Given that their sample is mainly composed by galaxies with disks, they claim that secular processes might have fuelled both a central bulge and correlated BH in time thus preserving their correlation down to z = 0. More generally, other additional sources of BH fuelling at later times are also probably at work, such as winds from stars (e.g., Ciotti & Ostriker 2001;Kauffmann & Heckman 2009;Cen 2012, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Given that their sample is mainly composed by galaxies with disks, they claim that secular processes might have fuelled both a central bulge and correlated BH in time thus preserving their correlation down to z = 0. More generally, other additional sources of BH fuelling at later times are also probably at work, such as winds from stars (e.g., Ciotti & Ostriker 2001;Kauffmann & Heckman 2009;Cen 2012, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…The BCGs often host radio-loud AGN (Sun 2009), and theoretical estimates have long suggested that the mechanical heating of the intracluster gas by these AGNs plays a key role in counteracting radiative cooling (Binney & Tabor 1995;Ciotti & Ostriker 2001;Soker et al 2001;Babul et al 2002). With imaging X-ray observations showing clear signs of interactions between the AGN outflows and the hot diffuse gas surrounding the BCGs (see Nulsen 2007, 2012 andreferences therein), there is now a broad consensus that in order to make sense of the full range of BCG properties, it is crucial to understand the role of cooling, feedback and gas accretion in cluster cores.…”
Section: Introductionmentioning
confidence: 99%
“…Suggested explanations for this lack of nuclear activity have included the presence of Compton-thick obscuring material in the line of sight to the nucleus (e.g. the Circinus galaxy, Matt et al 1999), feedback modulated accretion with a low duty cycle (Binney & Tabor 1995, Ciotti & Ostriker 2001, and inefficient accretion onto the black hole (e.g., Sgr A*, see review by Melia & Falcke 2001. The latter include instability-driven periodic accretion in a thin accretion disk (Siemiginowska & Elvis 1997;Siemiginowska, Czerny & Kostyunin 1996), and the more popular radiatively-inefficient advection dominated accretion flow (ADAF, CDAF, ADIOS) models (see review by Narayan 2002).…”
Section: Introductionmentioning
confidence: 99%